LED-based Fourier transform spectroscopy of H217O in the range of 17000-20000 cm−1. 5ν, 5ν+δ and 6ν resonance polyads. (September 2021) - Sinitsa, L.N.; Serdyukov, V.I.; Polovtseva, E.R.; Bykov, A.D.; Scherbakov, A.P.
Highlights: The absorption Fourier spectrum of the Н2 17 О molecule have been studied in the visible spectral range from 17000 cm −1 to 20000 cm −1 for the first time. High sensitive LED-based FTS technique was used. New 159 transitions to a total of 20 upper vibrational states belonging to the 5ν, 5ν+δ, and 6ν polyads along with 107 energy levels have been determined. Abstract: We report measurements and analysis of the vibrational-rotational absorption spectrum of the Н2 17 О molecule in the visible range from 17000 to 20000 cm −1 . Measurements were carried out using an IFS-125M Fourier spectrometer with a resolution of 0.1 cm −1, at a pressure of 24 mbar, a temperature of 25 ° С, and an optical path length of 24 m. A CREE XPE GRN LED, having its maximal radiation intensity in the region of 520 nm, was used as a source of radiation. The spectra were identified using calculations of the EXOMOL group [Polyansky et al Mon Not R Astron Soc 2017;466:1363–1371]. The least squares fitting method was used to determine the parameters of the Voigt profile: the line centers, intensities, and half-widths. The spectrum analysis produced a line list that contained 159 lines of the Н2 17 О molecule in the studied region and a set of 107 experimental energy lines. We compare the obtained experimental data on the absorption of the Н2 17 О molecule with the calculated data of other authors.